Identifying factors affecting the creation of brand identity in Iran's banking industry - Seyed Mahdi Saatchi; farzad asayesh; Sedighe Tootian Esfahani; Seyed Mahmood Hashemi (ارزش آفرینی در مدیریت کسب و کار, 2024)
AbstractThe purpose of this research is to identify the factors influencing the creation of brand identity in the banking industry of Iran. According to its purpose, the research method is applicable, and in terms of implementation, it is qualitative and based on the case study approach. The statistical population of this research includes Iranian banking industry experts who were senior managers of Bank Mellat in Tehran. The number of 23 experts who had sufficient knowledge and expertise in the field of brand was selected by judgmental sampling and snowball method, and data collection was done using semi-structured interview tool. The interviews were continued until theoretical saturation was reached, and the text of the interviews were analyzed and coded using the MAXQDA 2018 software. Data analysis led to the identification and extraction of research findings including 130 primary codes, 33 concepts, and 10 categories. Based on the results of this research, the categories of goals and strategies, structure and processes, human resource management, organizational culture, internal branding, communication, banking services, financial power, visual identity, and verbal identity are identified as the important factors affecting the creation of identity in the banking industry of Iran.Extended Abstract                                           IntroductionOne of the fundamental concepts in the field of brand is the issue of brand identity. Brand identity affects business performance, employees' recognition of the organization, and the special value of the brand (Fan, Hsu & Xiaofeng, 2023). This phenomenon is initially formed at the business level and needs to be recognized, received and accepted by customers (Liu, Hsu, Fan, 2020). Brand identity determines both the goals of the brand and the paths to be followed by the organization (Krissanya & Widyaningsih, 2023) and tells stakeholders what is unique about the brand (Sarasvuo, Liljander & Haahtela, 2023). Brand identity and brand image are two important components related to the brand; brand identity determines what the brand talks about, and brand image tells how the brand is heard by customers (Clottey, Gyampoh & Anaba, 2023). In service organizations and especially banks, employees' attitude and behavior play an important role in the bank's performance, and employees are the main link between the brand and customers by responding to customers' requests (Lee, Hsiao & Chan, 2019). Today, due to the significant increase in competition among banks in the country, most banks seek to create a unique position for their brand in order to be distinguished from other competitors. One of the most basic concepts related to branding is the creation of brand identity; therefore, having a desirable brand identity can be considered an effective differentiator. The main problem of this research is to identify the factors that influence the creation of brand identity in the banking industry of Iran.LiteratureThe brand identity expresses the ideal characteristics that the brand intends to provide to the customers. In other words, brand identity is what the brand has promised to deliver to the market (Behrozi & Sohrabi, 2022). The visual identity of the brand includes items such as the brand logo, product and packaging, buildings, clothing and appearance of employees, and other such items. A brand logo is a sign that consists of a unique combination of letters, fonts, shapes, colors or symbols, and its purpose is to visually identify the brand (chernev, 2018). Significant increasing of competition in the business domain has led to the boost and growth in establishing, maintaining and expanding brand communication with customers has been growing. On the other hand, the widespread use of information technology in businesses has created new ways to communicate with customers (Farmani, Ghaffari & Zandi, 2020). A sustainable brand identity emerges from the actual organizational identity and the culture in which the brand concept is institutionalized (Andersen et al, 2023). Since the way employees deal with bank customers and the way they provide service to customers and even the way the employees dress and groom their appearance has an impact on how the bank's brand identity is formed (Behrozi & Sohrabi, 2022), therefore internal branding plays an important role in creating brand identity.Clottey, Gyampoh & Anaba (2023) have conducted a research on the effect of brand identity and brand image on fashion entrepreneurs. The findings of the research show that the brand name affects the purchase decision of their customers, and the brand identity increases the awareness of investors and customers and customer loyalty. Also, the effect of brand image and brand identity such as logo, symbol, color and other things significantly affects customer loyalty.Behrozi & Sohrabi (2022) in a research entitled "the role of perceived value and brand identity in improving customers' attitudinal loyalty" investigated 384 customers of Melli and Tejarat banks in Mazandaran province. The results showed that perceived value plays a mediating role in the relationship between brand identity and customers' attitudinal loyalty.Rezaeian & Asgari (2021) in a research entitled "the effect of ethical marketing on consumer repurchase intention with emphasis on the mediating role of brand identity and brand value" studied Digi Kala online store. The results showed that ethical marketing with the mediating role of brand identity variables and brand equity has a positive and significant effect on customers' repurchase intention.Research method This research is applicable in terms of its purpose, and qualitative in terms of execution method, and is a case study type. Field method was used to obtain data, and semi-structured interview tools and in-depth interview sessions were used to collect data. The statistical population of this research was the senior managers of Bank Mellat as experts in the banking industry. 23 of these experts were selected and interviewed by judgmental and snowball sampling methods. MAXQDA 2018 software was used to analyze the content of the interviews.Research findingsAt the beginning of the analysis, the researcher has started to code the interviews in order to obtain the effective factors on the creation of the brand identity. Primary codes with common meanings are placed together and create concepts, and a category is formed from the combination of several concepts. In the first stage of coding, 130 primary codes were identified; then these codes were categorized into 33 concepts and 10 categories. Based on the analysis, the factors affecting the creation of brand identity in the banking industry (the same categories found) are: goals and strategies, structure and processes, human resource management, organizational culture, internal branding, communication, banking services, financial strength, visual brand identity, and verbal brand identity. DiscussionThis research was conducted with the aim of identifying the factors influencing the creation of brand identity in the banking industry of Iran. The results of this research are aligned and somewhat consistent with the findings of researchers such as Daneshgar et al, (2020), Yazdanshenas et al, (2022), Sharma et al, (2022), Krishna & Kim (2021), and Chung & Byrom (2021). The goals and strategies that a bank undertakes directly affect the creation of its brand identity. The flexibility of banks' structure can play an important role in a bank's brand identity. The way managers interact with employees is one of the things important in the field of organizational interactions. Organizational culture is defined by concepts such as the attitude and behavior of employees as well as the attitude and behavior of managers. Internal branding activities, focusing on employees, try to introduce the main concepts, essence, values and functions of the organization's brand to them, so that employees can have a correct understanding of their organization's brand. Communication with society and customers, maintaining human values and respect for customers by branch employees, as well as close interaction with customers by managers can strengthen the bank's relationship with its customers. The diversity of banking services and the provision of innovative and high-quality services to customers can create the brand identity of a leading bank. Also, the financial ability to grant large facilities is a factor that explains the bank's brand identity in the society. The tone of the brand in direct and indirect interactions, including the types of advertisements in different media, the type of brand slogan, the way of addressing the society in different media and choosing the right words and expressions, induces the brand identity of a bank to the audience. The characteristics of a bank's buildings, from the extent and number of its branches to the beauty of the facade of the building and the signs of the branches and the interior of the branches, express the visual identity of the bank's brand.Based on the results of the research, it is suggested that banks create their desired brand identity by creating a competitive advantage via focusing on providing services needed by customers and also by improving the level of customer orientation by employees. Strategies such as cost management and the growth of Rial and foreign currency incomes, attracting low-cost bank deposits, facilitating the provision of services to customers are among the important things in creating a professional brand identity for the bank. Improving leadership qualities and knowledge of human resources in managers is also a requirement for creating brand identity in banks. Also, part of the bank's recruitment can be done with new mechanisms with the aim of attracting the country's scientific elites and using them in the direction of innovative and transformational movements in the banking industry. In the field of organizational culture, it is necessary to promote value-oriented behaviors based on concepts such as loyalty and commitment to the bank, customer-orientedness, honesty and ethics in dealing with customers and employees. Implementing various intra-organizational campaigns with the aim of disseminating brand concepts and values, causes employees to participate in brand-oriented issues and reward top employees increases the level of loyalty and belongingness of employees to their bank brand. It is necessary for banks to review their structure and remove and modify redundant parts as much as possible so that processes can be implemented more quickly and agilely. Focusing on the development of digital banking is also one thing that can be effective in creating and establishing a desirable brand identity in banks due to the promotion of issues related to digital transformation. In the field of visual identity, updating the bank's logo and font, significant change in the appearance of the branches, having an identifying color specific to a bank, and using uniforms for employees are among the important things to create a brand identity in a bank. Preparing and communicating a verbal standard for employees to communicate with customers can be effective in improving the brand's verbal identity.